Innovation in Lecturer Communication in Managing Graduate Learning at UIN Alauddin During the Pandemic - Yuliana, Yuliana; Saat, Sulaiman; Mania, Sitti (Jurnal Mercusuar, 2021)
This research discusses the teaching innovation of postgraduate lecturers at UIN Alauddin Makassar during the pandemic. This study used a qualitative descriptive research method with a case study approach, and was conducted in the Islamic Education Master's Program at UIN Alauddin Makassar for the 2020 academic year. Data was collected through observation, interviews, and documentation. The results of the study indicate that the innovation of postgraduate lecturers at UIN Alauddin Makassar during the pandemic has been maximized, but the impact or results of the innovation have not been optimal due to several factors that affect the students, such as network disruptions during student presentations, insufficient internet quota causing delays, and some lecturers not being familiar with the learning platforms used during the pandemic. The management of learning carried out by lecturers in the Islamic Education postgraduate program at UIN Alauddin Makassar has not been optimal due to limited flexibility in monitoring students' gestures online during the learning process and the inadequate delivery of materials to students. The teaching innovation of postgraduate lecturers at UIN Alauddin Makassar in managing learning during the pandemic has been less effective due to several students being affected by network disruptions during the learning process, some students not following the lessons properly, and students who are not focused on receiving the materials, resulting in a failure to achieve the intended learning outcomes.